2021
DOI: 10.1111/opo.12826
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of sunlight exposure against PRK‐induced myopia in infant rhesus monkeys

Abstract: Purpose: Extensive clinical evidence suggests that time spent outdoors might reduce the risk of myopia. This study aimed to determine whether increasing sunlight exposure has a protective effect on hyperopic-defocus induced myopia in a non-human primate. Methods: Twelve 2-month-old rhesus monkeys were treated monocularly with photorefractive keratectomy (PRK) (4.0 D) and divided randomly into two groups: artificial light (AL; n = 6) and natural light (NL; n = 6). Monkeys in the AL group were reared under artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…But exposure to sunlight for 3 hours a day signi cantly reduced the progress of refractive myopia in normal eyes and negative lens-induced eyes of young monkeys. [41] Similar ndings were also con rmed in the research conducted by Yang et al [42] Considering the signi cant difference in light levels and spectral composition between indoor and outdoors, and the theory that relative myopic defocus over a large portion of the retina have been shown to produce clinically meaningful reductions in myopia progression. [43][44][45] In their opinion, the protective effect of increasing outdoor time on myopia is also related to spectral components and the mechanisms might be both complex and phase-dependent.…”
Section: Discussionsupporting
confidence: 66%
“…But exposure to sunlight for 3 hours a day signi cantly reduced the progress of refractive myopia in normal eyes and negative lens-induced eyes of young monkeys. [41] Similar ndings were also con rmed in the research conducted by Yang et al [42] Considering the signi cant difference in light levels and spectral composition between indoor and outdoors, and the theory that relative myopic defocus over a large portion of the retina have been shown to produce clinically meaningful reductions in myopia progression. [43][44][45] In their opinion, the protective effect of increasing outdoor time on myopia is also related to spectral components and the mechanisms might be both complex and phase-dependent.…”
Section: Discussionsupporting
confidence: 66%
“…Prolonged near work and very limited outdoor exposure has been considered to contribute to current pandemic of myopia in Asian children. A recent animal experiment has demonstrated that natural light exposure provides a protective effect against myopia development by more hyperopic refraction and shorter vitreous chamber depth [40]. Since the mechanism of emmetropization is contained within the eye and peripheral defocus can alter refractive development [16], the defocus experienced by the peripheral retina would be expected to drive eye growth [13].…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional analysis within the Singapore birth cohort study, more time outdoors, but not light levels or the timing and frequency of light exposure, was associated with lower odds of myopia [ 237 ]. Another study found that greater green space coverage was associated with lower prevalence of myopia [ 238 ]. While more time outdoors seems well-established as protective for the development of myopia, details of optimal exposure to minimise myopia are not fully elucidated.…”
Section: Benefits Of Exposure To Uv Radiationmentioning
confidence: 99%